Ответы и объяснения

  • Участник Знаний
2015-11-19T11:34:45+03:00
А) (SinxCosπ/3 - CosхSin π/3)(Cos xCosπ/6 + SinxSinπ/6) =1
(1/2 Sinx -  √3/2Сos x)(√3/2Сosx + 1/2Sinx) = 1
1/4Sin²x - 3/4Сos²x = 1
1/4Sin²x - 3/4Cos²x = Sin²x + Cos²x 
1/4Sin²x - 3/4Cos²x - Sin²x - Cos²x =0
-3/4Sin²x - 7/4Cos²x = 0 | ·(-4)
3Sin²x +7Cos²x = 0
3Sin²x + 7(1 - Sin²x) = 0
3Sin²x +7 -7Sin²x = 0
4Sin²x = 7
нет решений.
б)Есть формула: 2SinαCosβ = Cos(α-β) -Cos(α + β)
Наше уравнение:
1/2(Cosx - Cos2x) = 1/2
Cos x - Cos 2x = 1
Cosx -(2Cos²x -1) - 1=0
Cos x - 2Cos²x +1 -1 = 0
Cos x - 2Cos²x = 0
Cosx(1 - 2Cos x) = 0
Cos x = 0              или             1 - 2Cos x = 0
x = π/2 + πk , k ∈Z                   Cos x = 1/2
                                                  х = +-arcCos 1/2 + 2πn,n∈Z
                                                   x = +- π/3 + 2π n, n∈Z
в)Учтём, что Sin(π/4- x) = Cos(π/2 -(π/4 -x)) = Cos(π/3 +x)
наш пример:
2Sin(π/4 +x)Cos(π/4+x) = 0
Sin(π/2 +2х) = 0
Сjs 2x = 0
2x = π/2 + πk, k ∈Z
x = π/4 + πk/2, k ∈Z